Evaluación de un proceso de recuperación de uno de los metales presentes en las tarjetas de circuitos impresos (2017)
Approximately 60 printed circuit boards were contributed by the company Patrix Technology, for the development of this degree work; These cards were subjected, firstly, to a process of cleaning and disassembling the electronic components that were connected to each one of them; After this, the particle size reduction of the cards was carried out, obtaining a particulate material of approximately 690 g. Through a series of granulometric tests, it was possible to know the particle size distribution of particulate material obtained, to a representative sample of printed circuit particles, the X-ray fluorescence test was carried out in the company Xamtec S.A.S. Knowing this way, the metallic composition of the material. After an extensive literature review of different methods of recovery of some of the metals present in printed circuit boards, the alternative to be used was selected, using the method of selection of alternatives by weighted sums, it was chosen that the method of recovery of copper to be developed is that which consists of acid leaching using H2SO4 and H2O2.